2016
DOI: 10.1021/acs.jpcc.6b04729
|View full text |Cite
|
Sign up to set email alerts
|

[Py1,4]FSI-NaFSI-Based Ionic Liquid Electrolyte for Sodium Batteries: Na+ Solvation and Interfacial Nanostructure on Au(111)

Abstract: In this paper, the NaFSI-[Py 1,4 ]FSI/Au(111) interface was investigated using cyclic voltammetry (CV) and in situ atomic force microscopy (AFM). Raman spectroscopy was used to evaluate the Na + solvation in [Py 1,4 ]FSI. It was found that Na coordinates with three FSIforming [Na(FSI) 3 ] 2-. In situ AFM revealed that the interaction of [Py 1,4 ]FSI with Au (111) is much stronger compared to other ionic liquids measured using the same technique. On applying a potential, a force of about 50 nN is required to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 32 publications
12
58
1
Order By: Relevance
“…6c for Na salt concentration dependency) 79,84,116,119,125,126,135,180 and tend to increase with increasing Na salt concentration in the Na[FSA]-[C 3 180 Molecular dynamics simulations have indicated that clustering of Na + and FSA À ions occurs at high Na[FSA] concentrations, 79,181 enabling site exchange and/or indicates a structural diffusion mechanism for Na + , leading to high transport numbers. Clustering of Na + and FSA À ions and rapid exchange of the Na + ion between different coordination environments have also been suggested in this and analogous IL systems by Raman spectroscopic, 180 NMR spectroscopic, 79,182 and atomic force microscopic 182 studies.…”
Section: Physicochemical Propertiesmentioning
confidence: 53%
“…6c for Na salt concentration dependency) 79,84,116,119,125,126,135,180 and tend to increase with increasing Na salt concentration in the Na[FSA]-[C 3 180 Molecular dynamics simulations have indicated that clustering of Na + and FSA À ions occurs at high Na[FSA] concentrations, 79,181 enabling site exchange and/or indicates a structural diffusion mechanism for Na + , leading to high transport numbers. Clustering of Na + and FSA À ions and rapid exchange of the Na + ion between different coordination environments have also been suggested in this and analogous IL systems by Raman spectroscopic, 180 NMR spectroscopic, 79,182 and atomic force microscopic 182 studies.…”
Section: Physicochemical Propertiesmentioning
confidence: 53%
“…The same is true for the Raman bands observed in C 2 mim[TFSI] and C 4 mim[TFSI] systems which together with DFT calculations suggest the presence of predominantly [Na(TFSI) 3 ] 2‐ . Similar complexation has been reported for the [FSI] − anion in the NaFSI/C 4 mpyr[FSI] system using Raman and AFM techniques . NMR studies of NaTFSI/N 2(2O2O1)3 [TFSI] and the mixed anion system (NaFSI/N 2(2O2O1)3 [TFSI]) suggest a similar coordination environment for Na + since diffusion in both systems was similar…”
Section: Novel Physicochemical Properties For Na Energy Storagementioning
confidence: 99%
“…As ionic liquids are promising electrolytes for applications containing metallic components such as batteries or electrodeposition, many AFS studies have been performed that focus on the formation of the interface structure in the presence of the dissolved metals. Endres et al [115] [116] reported that the interfacial multilayer structure is not significantly affected after adding small amounts of Na. However, when adding more than 0.25 M of Na, the innermost layers changed, indicating the local formation of [Na(FSI) 3 ] 2− .…”
Section: Addition Of Metallic Solvatesmentioning
confidence: 99%